Development of a STEM and Moral Education-Based Pocketbook: A Literature Review of Its Role in Enhancing Students' Scientific Literacy and Social-Emotional Skills - Fitri Yeni; Muhyiatul Fadilah; Rahmawati Darussyamsu (Bioeducation Journal, 2026)
The ethnoscience study has become an important approach in revealing the relationship between local knowledge and modern scientific concepts, particularly in traditional food processing practices. One form of this local wisdom is reflected in a typical Minangkabau dish, dendeng pucuk ubi, which is developed in Nagari Simarasok. This study aims to analyze the ethnoscientific elements contained in the processing of dendeng pucuk ubi and to examine the scientific and cultural values underlying it. The method used is qualitative research with an ethnographic approach, employing observation techniques, in-depth interviews with local communities, and documentation. The results show that the processing of dendeng pucuk ubi is not merely a culinary activity but also contains scientific principles, including biological aspects (nutritional content of cassava leaves as a source of fiber, vitamins, and minerals), chemical aspects (changes in compounds during cooking and drying processes), and physical aspects (the influence of temperature and processing techniques on texture and shelf life).In addition, this practice reflects local wisdom values such as sustainable utilization of natural resources, togetherness in the cooking process, and preservation of the cultural identity of the Simarasok community. Therefore, dendeng pucuk ubi is valuable not only as a food product but also as a medium for integrating culture and science, which is relevant for the development of contextual learning. This research is expected to contribute to strengthening ethnoscience-based education as well as preserving traditional culinary heritage.